Gelation performance of PAM/PEI polymer gel with addition of retarder in high-salinity conditions - Amir, Z. (Springer, 2022)
The complex nature of heterogeneous reservoirs requires the development of effective and stable polymer gel to reduce excessive water production. Organically cross-linked polymer gel is becoming popular and an effective means of conformance control. The key objective of gel treatment is to reduce the flow of water through high-permeability channels and divert the subsequent injection water to the productive zones of the reservoir. This article briefly studied the effects of salinity and NH4Cl as retarders on the performance of the PAM/PEI polymer gel, especially the effects on viscosity, gelation time, gel strength, and gel morphology. The experimental results show that the effectiveness of NH4Cl to extend the gelation time of polymer gel is significantly reduced in high salinity. With the increase of salinity, the gel network greatly loses its gel strength as well. This indicates that a weak gel structure is formed and becomes vulnerable as observed from the surface morphology. It can be observed that PAM/PEI gel with NH4Cl in high salinity has a certain granular structure in some regions. These findings provide a better understanding and give additional insight as current studies have not significantly described the performance of PAM/PEI polymer gel with NH4Cl as a retarder that was prepared in high salinity for high-temperature water control application. Figure not available: see fulltext. Â© 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.